Analisa UI Website “Balinesia” Sebagai Sarana Rekomendasi Wisata di Bali Menggunakan Metode SUS - Martayasa, I Gede; Karyawati, Anak Agung Istri Ngurah Eka (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 1 (2022): JNATIA Vol. 1, No. 1, November 2022, 2022)
User interface is one of the most important factors in building a website. A good user interface has aspects of clarity, conciseness, easy to recognize, responsiveness, consistency and has aesthetic content. Without careful preparation and design, a certain website cannot run optimally, it can even cause users to move to other websites. The purpose of this study is to analyze the quality of User Interface design in the Web-Based Tourist Destination Recommendation Application in Bali Province. User Interface design quality analysis will be carried out using the SUS method or System Usability Scale. Quality evaluation on the usability aspect was carried out using the SUS questionnaire as an assessment standard. The results of this assessment will determine whether or not the UI design is feasible on the Web-Based Tourist Destination Recommendation Application in Bali Province.